2014
DOI: 10.1007/s13311-014-0270-5
|View full text |Cite
|
Sign up to set email alerts
|

Prestroke Statins, Progression of White Matter Hyperintensities, and Cognitive Decline in Stroke Patients with Confluent White Matter Hyperintensities

Abstract: Cerebral white matter hyperintensities (WMH) are a consequence of cerebral small vessel disease. Statins have been shown to reduce recurrent stroke among patients with various stroke subtypes, including lacunar stroke, which also arises from small vessel disease. In this study, we investigated the hypothesis that prestroke statin use would reduce the progression of WMH and/or cognitive decline among stroke patients with confluent WMH. Patients (n=100) were participants of the VITAmins To Prevent Stroke magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 24 publications
4
46
0
Order By: Relevance
“…This study also found that BMI was significantly associated with MCR in the French cohort, as demonstrated in previous work [3]. The prevalence of WMH was also consistent with previous studies [14, 22, 24, 3944]. However, the French cohort did have a higher prevalence of WMH overall.…”
Section: Discussionsupporting
confidence: 92%
“…This study also found that BMI was significantly associated with MCR in the French cohort, as demonstrated in previous work [3]. The prevalence of WMH was also consistent with previous studies [14, 22, 24, 3944]. However, the French cohort did have a higher prevalence of WMH overall.…”
Section: Discussionsupporting
confidence: 92%
“…124 For statin treatment, trials have provided conflicting evidence as to whether statin treatment reduces WMH progression. [125][126][127] Intensive glucose-lowering therapy in patients with type 2 diabetes mellitus did not reduce WMH progression and in fact was associated with higher WMH progression for unclear reasons. 128 Vitamin B and folate therapy did not reduce the progression of WMH in the VITATOPS study (Vitamins to Prevent Stroke), although a significant reduction in WMH progression (0.3 versus 1.7 cm 3 ; P=0.04) was detected in patients with severe WMH at baseline.…”
Section: Vascular Risk Reduction In Patients With Wmh To Prevent Sympmentioning
confidence: 99%
“…Vascular preventive therapy primarily reduces acute vascular events, for example, stroke and myocardial infarction,11 but may also limit chronic vascular damage. Following stroke, statins reduced white matter hyperintensity progression rates, and limited the decline in executive function 34. In AD, observational data suggested that treating vascular risk factors altered the rate of cognitive decline, although one can argue such studies are subject to bias 35.…”
Section: Discussionmentioning
confidence: 99%